The state of the art of Chromadoridae (Nematoda, Chromadorida): a historical review, diagnoses and comments about valid and dubious genera and a list of valid species - Venekey, Virag; Gheller, Paula F.; Kandratavicius, Noelia; Cunha, Beatriz Pereira; Vilas-Boas, Ana Carolina; Fonseca, Gustavo; Maria, Tatiana F. (Zootaxa, 2019)
Chromadoridae is a widespread family of mostly free-living marine nematodes. This systematic review provides for each genus: a historical background, an updated diagnosis and a list of species. Our review recognizes 37 valid genera, 395 valid species, 57 descriptions without enough morphological information for accurate identification (species inquirenda) and 10 species incerta sedis. We also recognize 21 species as nomena nuda. Additionally, polytomous keys were constructed for the subfamilies and for the genera of the three major subfamilies (Chromadorinae, Euchromadorinae and Hypodontolaiminae) using the most important diagnostic characters. A phylogenetic analysis based on rDNA sequences of species available in the GenBank was also conducted. Phylogenetic trees based on the 18S and 28S rDNA confirmed the classification into three subfamilies (Spilipherinae, Hypodontolaiminae and Chromadorinae), despite the absence of defined synapomorphies. Phylogenetic relationships at lower taxonomic level are problematic given the large number of sequences not identified to species level.